Mode Dan Sarana Pelaporan Dari Tiga Perspektif Utama: Post- Strukturalisme, Humanisme, Dan Ilmu Sosial. - Rizal Maulana (Journal of Innovative and Creativity, 2025)
This article examines the modes and means of reporting from three main perspectives: post- structuralism, humanism, and social sciences. Through in-depth theoretical analysis, this article explores how reporting is not only a tool for information, but also a construction of power, human values, and social practices. This approach reveals the complexity of reporting in the context of modern media, with implications for journalistic ethics and social transformation. The discussion is expanded with empirical examples, theoretical critiques, and practical applications.